COVID-19 pathology and therapeutics - Sorour, Khaled; El Menshawy, Hadeer (My University, 2020)
The SARS-CoV-2 pandemic has hit the world by surprise since its first outbreak in Wuhan, China resulting in millions of cases and thousands of deaths around the globe. The current situation is challenged by the lack of knowledge about the COVID-19 pathogenesis. Experts are not sure about the primary driver for mortality, is it the virus or the host immune response. The highly noted difference in outcomes reflects that individuals could react uniquely in response to infection where the inflammatory processes appear to impact the course and outcome of infection. Moreover, findings that came from COVID-19 autopsies suggest that SARS-CoV-2 pneumonia could transform to a severe form of ARDS. This paper aims at addressing briefly various complications observed in COVID-19 patients and providing a list of drugs that could be incorporated as a part of standard care for patients that are most severely affected by SARS-CoV-2 infection.
Keywords: ARDS; COVID-19; Inflammation; Pathology; SARS-CoV-2; Therapy